Kasus ambalat-reaksi media Indonesia: framing dan komunikasi antarabangsa - Lai, Che Ching@Abd.Latif; Lee, Kuok Tiung (2007)
This journal is a preliminary effort to analyse the reactions of selected Indonesian media on the struggle of Malaysia and Indonesia pertaining to the Ambalat case. The issue has been debated heavily due to continuous provocation by the Indonesian media. Hence, a content analysis study, both qualitative and quantitative is undertaken to study further the process of news framing by Indonesian media on the Ambalat case. Findings from the study showed that the Indonesian media tend to use dplomatic and war frames when discussing the issue. Political elite groups, the government and Indonesian National Army are the main sources of news used. The findings also indicate that the selected Indonesian media tend to put aside their own national interest in covering international news that involved Malaysian interest.